2013
DOI: 10.1007/s11664-013-2917-0
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Enhancing the Thermal Durability of High-Temperature Thermoelectric Materials

Abstract: Thermoelectric materials such as Skutterudites and Magnesium Silicides are being investigated as promising alternatives for medium to high temperature waste heat recovery in the transport sector and industry. A critical success factor for the thermoelectric material is its stability over time when exposed to rapid heating and cooling during its lifetime. In this work the different degradation issues at high temperature are examined for these thermoelectric materials, and several means of enhancing durability h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 20 publications
1
32
0
1
Order By: Relevance
“…The sample exhibited only clear Bragg peaks from the face‐centered cubic (fcc) antiflourite structure with the space group Fm3m. Throughout all three aforementioned synthesis stages, a weak diffraction peak at 2θ ≈ 43° represents a small amount of MgO impurity. This is a common impurity for all Mg 2 Si‐based materials, as Mg is volatile and highly reactive to residual oxygen at high temperatures via the oxidation process of every type of Mg 2 Si‐based compounds . The amount of MgO is more or less the same after the two heating stages, but a small increase is monitored on the powdered samples of the sintered pellets.…”
Section: Resultsmentioning
confidence: 99%
“…The sample exhibited only clear Bragg peaks from the face‐centered cubic (fcc) antiflourite structure with the space group Fm3m. Throughout all three aforementioned synthesis stages, a weak diffraction peak at 2θ ≈ 43° represents a small amount of MgO impurity. This is a common impurity for all Mg 2 Si‐based materials, as Mg is volatile and highly reactive to residual oxygen at high temperatures via the oxidation process of every type of Mg 2 Si‐based compounds . The amount of MgO is more or less the same after the two heating stages, but a small increase is monitored on the powdered samples of the sintered pellets.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5] However, the thermal stability issue of Mg 2 Si x Sn x solid solution is a major obstacle that must be tackled before the material can be applied in practical thermoelectric devices. [6][7][8][9][10] Tani et al found that Mg 2 Si starts to react with air signicantly above 723 K and the oxidation layer develops into the sample by oxygen diffusion. 6 Bourgeois et al studied the thermal stability of Mg 2 Si 1Àx Sn x solid solutions by in situ temperature X-ray powder diffraction in Ar gas.…”
Section: Introductionmentioning
confidence: 99%
“…8 Skomedal et al pointed out that in Mg 2 Si 1Àx Sn x compounds, Sn-rich solid solutions decompose faster at lower temperatures compared to the Si-rich solid solutions. 9 Yin et al examined the thermal stability of Mg 2 Si 0.3 Sn 0.7 in vacuum as well as in air. When heated at 773 K in vacuum, the Mg 2 Si 0.3 Sn 0.7 solid solution suffers a severe Mg loss due to the high vapor pressure of Mg; when heated in air without protection, the sample was oxidized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Inexplicably,t he effect of thermal cycling on the thermoelectric material itself is mostly neglected. Af ew investigations of bismuth tellurides [14,15] and skutterudites [16,17] can be found. Them ost detailed study on thermocyclic stability has the purpose of finding as tandardr eference material for Seebeckc oefficient measurements by comparing constantan to SiGe.…”
Section: Introductionmentioning
confidence: 99%